EVALUASI PELAKSANAAN DIGITALISASI PENYIARAN DI LPP TVRI STASIUN JAKARTA - Purwanto; Puji Lestari; Ade Wahyudin (Program Studi Ilmu Komunikasi, 2019)
TVRI Public Broadcasting Agency Jakarta Station has carried out preparations for digital broadcast trials in 2008 until now, but the transfer or migration of television broadcasting systems from analog to digital has not yet been able to take place due to several obstacles including issues related to government policies that delay the implementation of full broadcasts digital. This study aims to evaluate the implementation of broadcasting digitalization of LPP TVRI Jakarta station. This research uses a descriptive method. Data collection techniques are done by interview and observation. The results of this study were analyzed descriptively related to the implementation of digital broadcasting. The results of the research show that currently LPP TVRI broadcasts still use Analog and Digital equipment (Simulcast) because they are still waiting for the stipulation of regulations from the government to implement Switch on to Digital in 2020